Trend on E-Commerce Researches: A Portrait Using VOSviewer - Joko Hadi Purnomo; Niswatin Nurul Hidayati; Rizka Dibi Arryanti Saputri; Siti Riska Novianti (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
The e-commerce phenomenon has had a profound impact on various industries, including retail, logistics, and marketing. It has transformed traditional brick-and-mortar retail, leading to the rise of online marketplaces and the growth of direct-to-consumer (D2C) brands. E-commerce has also disrupted supply chain management, driving the need for efficient order fulfillment and last-mile delivery solutions. The objective of this research was to look at the global e-commerce research map. This research used bibliographic analysis with VOSviewer. The data source used was the Scopus database obtained from the https://www.sciencedirect.com/ page. Based on the VOSviewer visualization analysis, it could be seen that research on e-commerce globally was dominated in relation to digitalization, artificial intelligence, and Covid-19. This bibliographic study provided implications for researchers to see research gaps.